Reliability of Molecular Tests in Diagnosing Ovine Brucellosis Caused by Brucella Ovis - Zelenović Mladen; Marinković Darko; Stević Nataša; Stanojević Slavoljub; Aničić Milan; Milićević Vesna; Valčić Olivera; Radojičić Sonja (Acta Veterinaria, 2024)
Brucella ovis infects sheep and causes a clinical or subclinical disease characterized by genital lesions and reduced fertility in rams, placentitis and abortions in ewes, and increased perinatal mortality in lambs. As part of this study, analyses were conducted on a sheep farm near Belgrade (Serbia). Of the serological tests, indirect ELISA was performed. A total of 94 blood sera were analyzed, 33 from rams and 61 from ewes. The results showed 23 (69.7%) positive findings in rams and 2 (3.3%) positive findings in ewes, with an overall prevalence of 25.4% bounded by a 95% confidence interval. Bruce-ladder multiplex PCR and Real time PCR were performed on 19 serologically positive rams and two serologically positive ewes. The results indicate a slightly higher sensitivity of Real time PCR compared to conventional PCR in diagnosing B. ovis from the reproductive tissues of rams. However, the differences in sensitivity between different nucleic acid extraction protocols were not significant. Most rams showed a positive PCR result in only one sample of reproductive tissue, suggesting the recommendation to take multiple samples from each animal. Further research is needed to bring the sensitivity of molecular tests in diagnosing ram epididymitis closer to the sensitivity of serological tests.